Methionine Enkephalin Suppresses Osteocyte Apoptosis Induced by Compressive Force through Regulation of Nuclear Translocation of NFATc1 - Chisumi Sogi; Nobuo Takeshita; Wei Jiang; Siyoung Kim; Toshihiro Maeda; Michiko Yoshida; Toshihito Oyanagi; Arata Ito; Seiji Kimura; Daisuke Seki; Ikuko Takano; Yuichi Sakai; et al. (JBMR Plus, 2020)
ABSTRACT Mechanical stress stimulates bone remodeling, which occurs through bone formation and resorption, resulting in bone adaptation in response to the mechanical stress. Osteocytes perceive mechanical stress loaded to bones and promote bone remodeling through various cellular processes. Osteocyte apoptosis is considered a cellular process to induce bone resorption during mechanical stress‐induced bone remodeling, but the underlying molecular mechanisms are not fully understood. Recent studies have demonstrated that neuropeptides play crucial roles in bone metabolism. The neuropeptide, methionine enkephalin (MENK) regulates apoptosis positively and negatively depending on cell type, but the role of MENK in osteocyte apoptosis, followed by bone resorption, in response to mechanical stress is still unknown. Here, we examined the roles and mechanisms of MENK in osteocyte apoptosis induced by compressive force. We loaded compressive force to mouse parietal bones, resulting in a reduction of MENK expression in osteocytes. A neutralizing connective tissue growth factor (CTGF) antibody inhibited the compressive force‐induced reduction of MENK. An increase in osteocyte apoptosis in the compressive force‐loaded parietal bones was inhibited by MENK administration. Nuclear translocation of NFATc1 in osteocytes in the parietal bones was enhanced by compressive force. INCA‐6, which inhibits NFAT translocation into nuclei, suppressed the increase in osteocyte apoptosis in the compressive force‐loaded parietal bones. NFATc1‐overexpressing MLO‐Y4 cells showed increased expression of apoptosis‐related genes. MENK administration reduced the nuclear translocation of NFATc1 in osteocytes in the compressive force‐loaded parietal bones. Moreover, MENK suppressed Ca2+ influx and calcineurin and calmodulin expression, which are known to induce the nuclear translocation of NFAT in MLO‐Y4 cells. In summary, this study shows that osteocytes expressed MENK, whereas the MENK expression was suppressed by compressive force via CTGF signaling. MENK downregulated nuclear translocation of NFATc1 probably by suppressing Ca2+ signaling in osteocytes and consequently inhibiting compressive force‐induced osteocyte apoptosis, followed by bone resorption. © 2020 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.